2021
DOI: 10.1038/s41598-021-91501-y
|View full text |Cite|
|
Sign up to set email alerts
|

Osteogenic differentiation of human mesenchymal stromal cells and fibroblasts differs depending on tissue origin and replicative senescence

Abstract: The need for an autologous cell source for bone tissue engineering and medical applications has led researchers to explore multipotent mesenchymal stromal cells (MSC), which show stem cell plasticity, in various human tissues. However, MSC with different tissue origins vary in their biological properties and their capability for osteogenic differentiation. Furthermore, MSC-based therapies require large-scale ex vivo expansion, accompanied by cell type-specific replicative senescence, which affects osteogenic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 85 publications
1
13
0
Order By: Relevance
“…By the use of an IL-1R1/MyD88 inhibitor, the regenerative potential of MSCs could be improved. In cell culture studies, TGFβ, an anti-inflammatory cytokine, has inhibited the osteogenic differentiation of MSCs [49]. Similar has been reported for muscle cell differentiation [52].…”
Section: Mscs In Bone Diseasessupporting
confidence: 72%
See 1 more Smart Citation
“…By the use of an IL-1R1/MyD88 inhibitor, the regenerative potential of MSCs could be improved. In cell culture studies, TGFβ, an anti-inflammatory cytokine, has inhibited the osteogenic differentiation of MSCs [49]. Similar has been reported for muscle cell differentiation [52].…”
Section: Mscs In Bone Diseasessupporting
confidence: 72%
“…There seem to be various factors being involved in the regulation of MSCs and their regenerative capacity. In addition to cultivation, the origin of the MSCs is another important factor, because the osteogenic capacity can vary between cells due to the usage of different signaling cascades [49]. Nevertheless, MSCs are the most interesting agents in bone remodeling.…”
Section: Mscs In Bone Diseasesmentioning
confidence: 99%
“…These results indicate that Dll4 mRNA expression dynamics indicate two different stages during osteogenic differentiation: early differentiation stage (day 1day 5) and calcium mineralization stage (after day 5). It has been reported that the process of hMSCs osteogenic differentiation includes early lineage progression (proliferation), early differentiation, and later stage differentiation (calcium mineralization) [28,[30][31][32]. Our results indicate that Dll4 mRNA expression could potentially be the molecular signature of early osteogenic differentiation.…”
Section: Resultsmentioning
confidence: 53%
“…A comparative analysis demonstrated that MSCs obtained from bone marrow present a higher osteogenic differentiation potential than MSCs derived from adipose tissue, which are more adipogenic [ 15 ]. Similarly, dental pulp stromal cells displayed a greater capacity to differentiate into osteocytes than Ad-MSCs [ 58 ]. Another study found that umbilical cord blood MSCs possess a reduced capacity to differentiate into adipocytes, in contrast to BM-MSCs and Ad-MSCs [ 33 , 59 ].…”
Section: Changes Induced In Mscs During In Vitro Expansionmentioning
confidence: 99%